Edukasi dan Skrining Anemia Melalui Program Wish and Care di Desa Tosale - Susanto, Yuliet; Khaerati, Khildah; Widodo, Agustinus; Jamaluddin, Jamaluddin (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2025)
Anemia is a global problem, especially for adolescent girls and pregnant women. The high prevalence of anemia among adolescents increases susceptibility to disease in adulthood. Likewise, in pregnant women, anemia has the potential to cause complications in pregnancy and childbirth as well as maternal and child mortality. Increasing the knowledge of adolescent girls and pregnant women in efforts to recognize signs and symptoms of anemia, prevent and overcome anemia and motivation to undergo examinations related to anemia needs to be done. Therefore, community service activities are carried out to participate in educational efforts through the wish and care program in order to increase awareness and understanding of adolescent girls and pregnant women around the PKM area, namely Tosale village. The wish and care program is provided in the form of education, counseling, and practice, namely physical examination and Hb levels in 42 community service participants. Evaluation is carried out through pre-test and post-test. The results of the education showed an increase in knowledge in the good category of 71.43% and the sufficient category of 11.90%. The results obtained indicate that the wish and care method can increase public knowledge and awareness of early detection of anemia.